Were internal capital markets affected by the ‘perfect’ pension storm? - Alderson, Michael J.; Betker, Brian L. (Journal of Corporate Finance, 2009)
We examine capital expenditures in multi-segment firms before and after the “perfect storm” that affected pension plans between 2000 and 2002, when bond yields and stock prices both fell precipitously. Our sample of firms went from having overfunded to underfunded pension plans as a result of the storm. We examine the segment-level relation between investment, Tobin's q, and cash flow both before and after the event. We find mixed evidence on the change in the relation between investment and q, which may be a result of measurement error in q. We find stronger evidence for the conclusion that after the pension storm, firms with underfunded pension plans directed more investment towards segments that produce higher cash flow.